Irrigated farming and improved nutrition in Malawian farm households - Benson, Todd (International Food Policy Research Institute, 2018)
This chapter provides selected findings from an assessment of whether increased use in the dry season of irrigated farming by smallholders in Malawi might improve household-level dietary diversity or child nutrition outcomes. We find no strong association between the use of irrigation by farm households in Malawi and the growth performance of those households’ children. However, we do find that irrigating households tend to have more diverse diets than households that do not irrigate, leading to the hypothesis that irrigation enables households to produce a wider range of crops for home consumption than they can with purely rainfed production. In line with these results, we also find that irrigation reduces the negative effects of seasonal food insecurity. The insight we take from these findings is that one of the principal contributions that irrigation can make to improved nutrition outcomes, particularly for subsistence farming households, is to ensure reliable, year-round access to a diverse diet that facilitates access to micronutrient-rich foods, such as vegetables.